Enhancing Telecommunication Infrastructure Performance Through Dynamic Capabilities: The Mediating Roles of GRC Implementation and Artificial Intelegent Adoption - Tri Haryanto; Alfira Sofia (Green Publisher Indonesia, 2026)
The telecommunications infrastructure sector faces unprecedented challenges in balancing operational efficiency, regulatory compliance, and digital transformation amid capital-intensive investments exceeding USD 428 billion globally in 2023. This study investigates how telecommunication infrastructure organizations can enhance their performance through dynamic capabilities, examining the mediating roles of Governance, Risk, and Compliance (GRC) implementation and Artificial Intelligence (AI) adoption. Drawing on Dynamic Capabilities Theory (Teece et al., 1997) and the Resource-Based View (Barney, 1991), this research develops and tests an integrated framework using data from 87 telecommunication infrastructure organizations across 23 countries spanning 2019–2023. Structural Equation Modeling (SEM) was employed to analyze the relationships between dynamic capabilities, GRC implementation, AI adoption, and organizational performance using secondary data from annual reports, industry databases (ITU, GSMA Intelligence), and regulatory filings. The results reveal that dynamic capabilities significantly influence organizational performance both directly ( , ) and indirectly through GRC implementation ( , ) and AI adoption ( , ). GRC implementation and AI adoption exhibit complementary mediating effects, together explaining 68.3% of the variance in organizational performance ( ). The findings provide strategic guidance for telecommunication infrastructure managers to systematically develop sensing, seizing, and reconfiguring capabilities while concurrently strengthening governance frameworks and accelerating AI-enabled transformation. This research integrates dynamic capabilities theory with GRC and AI adoption frameworks, explicating mechanisms through which capabilities translate into superior performance in infrastructure-intensive sectors.